The design and performance of the Gravity Probe B telescope. (17th November 2015) - Wang, Suwen; Lipa, J A; Gwo, D-H; Triebes, K; Turneaure, J P; Farley, R P; Davidson, D; Bower, K A; Acworth, E B; Bernier, R J; Huff, L W; Schweiger, P F; et al.
Abstract: The Gravity Probe B spacecraft was launched on 20 April 2004 to measure the geodetic and frame-dragging effects predicted by the theory of general relativity. A cryogenic optical telescope was used to establish the inertial reference frame for the measurements by tracking a reference or guide star. The motion of this star was independently checked by reference to background galaxies. With the mission now over, we describe the design, construction and evaluation of the optical and electrical performance of the telescope, comparing ground and flight results. We find that the pointing noise was sufficiently low to meet the mission requirements and in fair agreement with extrapolations from ground tests. Due to slight defocusing, the linear range of the telescope output was significantly wider than expected.